Advances in the Prevention of Infection-Related Preterm Birth - Lamont, Ronald F. (Frontiers in Immunology, 2015)
Infection-related preterm birth is more common at early gestations and is associated with major neonatal mortality and morbidity. Abnormal genital tract flora in early pregnancy predicts late miscarriage and early preterm birth. Accordingly it is logical to consider antibiotics as an intervention. Unfortunately, the conclusions of systematic reviews and meta-analyses carried out to try to explain the confusion over the heterogeneity of individual studies are flawed by the fact that undue reliance is placed on studies with suboptimal choice of antibiotics (mainly metronidazole), used too late in pregnancy to influence outcome (23-27 weeks), in women whose risk of PTB is not due to abnormal genital tract colonization (previous preterm birth of indeterminate etiology, low BMI, or detection of fetal fibronectin, Ureaplasma spp., Group B streptococcus or Trichomonas vaginalis). While individual studies have found benefit of antibiotic intervention for the prevention of PTB, in meta-analyses these effects have been negated by large methodologically flawed studies with negative results. As a result, many clinicians think that any antibiotic given at any time in pregnancy to any woman at risk of preterm birth will cause more harm than good. Recently, a more focused systematic review and meta-analysis has demonstrated that antibiotics active against BV related organisms, used in women whose risk of PTB is due to abnormal flora, and used early in pregnancy before irreversible inflammatory damage has occurred, can reduce the rate of PTB. This review presents those data, the background and attempts to explain the confusion using new information from culture-independent molecular-based techniques. It also gives guidance on the structure of putative future antibiotic intervention studies.